TINJAUAN KOMPETENSI PROFESIONAL DOSEN : STUDI KASUS DI STKIP YAPIS DOMPU - Ilyas, Ilyas; Jaitun, Jaitun; Rizal, Syamsul (Prodi PAI STIT Sunan Giri Bima, 2023)
As the main agents of learning, lecturers and teachers have an important role in influencing the learning process and outcomes both in cognitive aspects, skills, attitudes and values ​​in students (students). Specifically, lecturers not only teach but are also scientists tasked with developing science and technology for society. As educators, lecturers (and teachers) are required to have four competency standards, namely pedagogical, personal, professional and social competencies. This qualitative research aims to determine the professional competence of STKIP Yapis Dompu lecturers. Professional competence is competence related to lecturers' teaching abilities. Data collection was carried out through interviews and document study. The primary data source is the results of the performance evaluation of STKIP Yapis lecturers in the field of learning for the 2021/2022 academic year. The collected data was then processed and analyzed descriptively. Of the 33 lecturers who were evaluated using 10 indicators, 24 people received a